Evaluate effect of deploying low-impact development on urban drainage systems - Loke, Si Min (2018)
Low impact development (LID) is a technology that enhances storm water runoff attain desired hydrologic conditions. The emergence of LID controls reduces the impact of urban development by effectively managing storm water runoff, improving water quality and protect environmental aspects of developed areas. However, discussion surrounding the cost-effectiveness of LID still entails. While past studies suggest that LIDs have been proven to reduce runoff effectively and improve water quality standards, insufficient studies have been done to account for the cost consideration to assist decision makers in choosing the most effective LID practice. This paper adopts the use of Storm Water Management Model (SWMM) to model the hydrologic performance of three forms of LID (Bioretention cell, Green roof and Permeable pavement) using six different combinations of LID controls. Results of hydrologic performance and water quality were attained and expressed in terms of percentage of decrement (%). In addition, cost of construction and rehabilitation cost of each case scenarios was determined using a costing tool by Toronto and Region Conversation (2013). Comparison will be made using the MCDA-AHP analysis to identify the most cost-effective case study. In this study, the combination of permeable pavement and bioretention cell has been identified to be the most effective case study. This study provides the methodology in assessing the best LID combination and discusses the effectiveness in terms of hydrologic performance, water quality and cost based on defined parameters and case studies. Therefore, the results obtained were case specific and any minor changes to the selected parameters could cause a change in results. Finally, recommendations and improvement of studies will be suggested for future research opportunities.